Complexion of Race : Categories of Difference in Eighteenth-Century British Culture - Wheeler, Roxann (New cultural studies., 2000)
"The Complexion of Race marks a decisive break with literary history's binary version of eighteenth-century British radical thought."--Journal of Social History